A Comparative Analysis of Minahasa Folklore Entitled Mamanua Lumalundung and Various Indonesian Folklores through Structuralism - Kobis, Dewi Christa; Marentek, Andriyani; Pamantung, Rina (Language Circle: Journal of Language and Literature, 2024)
This study is a comparative analysis that compares five Indonesian folklores that possess a theme of a love story between a mere human being and a fairy. The folklores are Mamanua Lumalundung, Jaka Tarub, Lengajan, Salambous, and Rajapala. This study focuses on finding the similarities and differences among these five. By implementing Robert Stanton’s Structuralism theory in analyzing the data, it is found that they have similarities and differences in the characters or characterizations, plot, setting, and point of view. The similarity among the characters lies on the existence of a regular man and a fairy while the differences lie in their attitude, power, and life priorities. The similarity that can be found in the plot is the love story between a regular man and a fairy while the differences focus on the problems that are described in each folklore and how they handle the situation. For the setting, the similarity is the time setting which is ancient time while the differences are only the description of lakes, forests, and kingdoms. Lastly, the similarity of the point of view is being delivered by the third singular person while only Lengajan and Salambous use the first singular person in the dialogue.